SPECIAL PRINCIPLE OF RELATIVITY - Vartanyan, Yu. L. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2005)
The review is dedicated to the centenary of creation of special theory of relativity. It concerns the basic statements of this theory. The article has a scientific cognitive and methodological character.
Keywords: theory of relativity; basic statements